1985
DOI: 10.1111/j.1600-0722.1985.tb01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Veadent as a plaque‐inhibiting mouthwash

Abstract: Abbas DK, Thrane P, Othman SJ: Effectiveness of Veadent as a plaque-inhibiting mouthwash. Scand J Dent Res 1985; 93: 494-7. Abstract ~ The aim of this study was to compare the effect of the commercially available Veadent mouthwash and chlorhexidine on plaque formation. Plaque accumulating during two 5-day periods was recorded in a group of 10 students. During the experimental periods, the test subjects abstained from mechanical cleaning of the teeth, and chewed sucrose-containing chewing gum every 4th h in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Sanguinarine topically applied showed some improvement over water (mean plaque score 0.206 and 0.345 respectively), but it was still far short of ideal when compared to chlorhexidine in its plaque reduction capacity (mean 0.038). These findings support previous reports indicating the superior antiplaque quality of chlorhexidine compared to sanguinarine (Abbas et al 1985, Wennstrom & Lindhe 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Sanguinarine topically applied showed some improvement over water (mean plaque score 0.206 and 0.345 respectively), but it was still far short of ideal when compared to chlorhexidine in its plaque reduction capacity (mean 0.038). These findings support previous reports indicating the superior antiplaque quality of chlorhexidine compared to sanguinarine (Abbas et al 1985, Wennstrom & Lindhe 1986).…”
Section: Discussionsupporting
confidence: 92%
“…At the end of each test period, a washout period of two weeks was allowed during which the volunteers were instructed to resume their previous mechanical plaque control measures [2]. Examination procedures were performed on a dental chair in the Department of Preventive, Pedodontic Dentistry at the Faculty of Dentistry at AlMustansiriya University with the aid of a dental mouth mirror and a Williams periodontal probe.…”
Section: Negative Controlmentioning
confidence: 99%
“…A number of clinical studies have shown the effects of using mouth washes extracted from herbs such as Selvadora persica [1], Sanguinarina [2] Quercus infectoria [3] Capparis spinosa [4] and cinnamon in the prevention of dental plaque accumulation and subsequent gingival inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These arrangements gave a washout period of at 2 days for each subject between each treatment. (20,21) At (day 1), all volunteers received a final professional tooth cleaning, scaling and polishing with home care instruction that include three times daily tooth brushing with once dental flossing and were subsequently told to abstain all mechanical tooth cleaning effort for the next five days. They were asked to rinse, however, three times daily for one minute each time with 15 ml of distilled water mouth rinse or water extract of propolis 0.1%, 0.5% or ethanolic extract 0.5%, 1% or CHX 0.2%.…”
Section: C-study Designmentioning
confidence: 99%